2022
DOI: 10.3389/fphys.2022.1006179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hanger reflex on the cervical muscular activation and function: A surface electromyography assessment

Abstract: Introduction: Cervical muscular dysfunction is closely associated with disorders and neuromuscular diseases of the cervical spine, and the hanger reflex (HR) has the potential to become a rehabilitation method. The muscular electrophysiology mechanism of HR is unclear. This study aims to identify the impacts of HR on cervical rotators’ myoelectrical activity and function.Methods: We designed a self-control clinical trial, and asymptomatic volunteers were continuously included from 1 September 2021 to 30 April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…All the participants included in this study were right-handed. The difference in the UT and SCM muscle activity was also observed by Wang and Liu [36] during bilateral hanger reflex, as well as without it.…”
Section: Discussionsupporting
confidence: 59%
“…All the participants included in this study were right-handed. The difference in the UT and SCM muscle activity was also observed by Wang and Liu [36] during bilateral hanger reflex, as well as without it.…”
Section: Discussionsupporting
confidence: 59%
“…The study showed a significant increase in the FRR value of patients after training, suggesting that the FRR of patients with CNLBP was effectively corrected. [ 28 ] One reason for this is that Bduanjin training can enhance the recruitment potential of the erector spine muscle during flexion and improve its reactivity and contractility. Therefore, there is a significant increase in AEMG during flexion and extension.…”
Section: Discussionmentioning
confidence: 99%